PENGARUH GOOD CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI (Studi Pada Perusahaan BUMN Sektor Non Keuangan Yang Terdaftar di Bursa Efek Indonesia Periode 2014-2019) - Putri Israyani Fauziah; Rochmawati Andewi; Haryetti Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aimed to examine the effect of corporate governance, intellectual capital This study aimed to examine the effect of corporate governance, intellectual capital and leverage on firm value with profitability as mediating variabel. Bid-ask spread is used to measure the variabel information asymmetry. PBV is used to measure the variabel firm value. Score GCG is used to measure corporate governance variabel, VAIC is used to measure Intellectual Capital Variabel and DER is used to measure Leverage Variabel. The population of this research was non-financial BUMN firms listed in Indonesia Stock Exchange (IDX) in 2014-2019. The sample was determined with census sampling method.That obtained 18 sample firms. The type of data in this research was secondary data obtained from IDX. The analytical method used was Multiple Regression and Mediation Analysis. The results of this study concluded : GCG and Intellectual Capital does not significantly influence on Profitability,While Leverage has an effect on Profitability. Then GCG, Intellectual Capital and Leverage significantly influence on firm value, Profitability significantly influence on firm value, Then Profitability cannot mediate the effect of GCG and Intellectual Capital on firm value, While Profitability can mediate the effect of Leverage on firm value.Keywords: Good Corporate Governance, Intellectual Capital, Leverage, Firm Value, Profitability